The Formation and Development of the Legal Status of a Consumer of Paid Medical Services in the Russian Health Care System in the XVIII – Early XX Centuries - M. V. Soboleva (Сибирское юридическое обозрение, 2020)
The socio-economic situation in Russia over the past decades has undergone serious changes that could not but affect the health system. There have been prerequisites for the development of private medicine, which has been supported by the state. Currently, there is an increase in the share of medical services provided on a paid basis. Widespread private practice, covering the chronological period of the Russian Empire, was interpreted by the authorities in the Soviet period as a relic of the capitalist system, contrary to the basic principles of proper health care organization. The Soviet period of Russian history appears to us as a chronological gap, that is, a time gap that characterizes the specifics of the linear existence of paid medical services. In this regard, it seems relevant and timely to conduct research on the historical aspects of the formation and development of the legal status of consumers of paid medical services in the Russian Empire. In our opinion, such research is of both theoretical and practical interest. The first is due to the lack of development of this topic in the historical and legal literature. The second one will allow us to identify existing shortcomings in legal regulation in the sphere of public health protection based on the generalization of historical experience and formulate practical recommendations for improving the legislation of the Russian Federation in this area. From the perspective of this work, we aim to assess the legal status of consumers of paid medical services in the XVIII – early XX century, comprehensively examining such elements of legal status as rights, freedoms, interests and duties. The article analyzes the influence of belonging of the inhabitants of the Empire to a particular social group on the formation of the legal status of consumers of paid medical services. For the first time, the main types of rights of consumers of paid medical services are separated from the regulatory legal acts in the field of healthcare of the Russian Empire and formed into a group. Based on the results of a detailed analysis, we conclude that in the Russian Empire, the duties of consumers of paid medical services took priority over the rights, since it was believed that if the obligations were met, the rights would exist regardless of their formal Declaration. The analysis helps to understand the development of regulation of health ser-vices and allows us to draw historical parallels with the existing regulatory framework of the health care system in Russia.